A PREVIEW OF APHASIA RESEARCH IN MALAYSIA AND INDONESIA - Lian, Lau Yoke (PEOPLE: International Journal of Social Sciences, 2017)
The current research on aphasia in Malaysia can be divided into two areas. One is carried out by research personnel of medical units while the other is carried out by university lecturers with linguistic background. The research studies made by both parties are different in terms of research methods and research focus. The researchers at medical units normally carry out aphasia research on stroke patients in most cases. Aphasia is only regarded as one of the symptoms of stroke patients. On the other hand, university lecturers with linguistic backgrounds remove reasons for aphasia and focus on aphasia itself instead of discussing reasons for the occurrence of stroke among aphasic patients. Malaysia has various researchers from different backgrounds who focus on aphasia. The researcher has found a lot of relevant data in this area. Meanwhile, many students with a background in liberal art and science have engaged in research in this area and these include undergraduate students, graduate students, and doctoral students. There are more doctoral students graduating from foreign universities and majoring in aphasia than those graduating from local universities. There are many doctoral students who graduated from universities in London, New Zealand, and other places. The aphasic patients who have been studied are those who speak Malay, Arabic, Hindi language and Minangkabau respectively. However, it was really surprising to find that there is no documented research on Chinese aphasic patients. Although there are few Chinese students conducting research in this area, there were no Chinese aphasic subjects. The absence of Chinese aphasic patients could possibly be due to the researcher’s failure to speak or understand Malaysian Chinese or failure in searching for suitable Chinese aphasic patients.